Changes in High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL) and Cholesterol Concentration in Heavy Cannabis Users: A Single-Centre Study in Cusco, Peru - Cusihuaman, Sandro (2022)
“Background: The effect of cannabis on cholesterol and lipid balance has been reported for decades. However, there are conflicting reports on the reduction of low-density lipoprotein (LDL-C) and total cholesterol. The purpose of this study was to determine the immediate changes of Cannabis spp. consumption by pyrolytic route in heavy users. Methods: A cross-sectional study on 20 Peruvian heavy cannabis users (mean age: 31 ± 9.5 years). The inclusion criteria were males with an average weight of 50–70 kg, normal BMI, and having used cannabis, without association with other drugs, for at least one year with a high frequency per week (use: 4–7 days/week). High-density lipoprotein (HDL-C), LDL-C, and total cholesterol were evaluated 30 and 120 min after the administration of Cannabis spp. (~0.2 g by inhalation). Results: Of the total 12 (60%), 10 (50%), and 11 (55%) had desirable total cholesterol, fairly good HDL-C (40–60 mg/dL) and fairly good LDL-C (100–129 mg/dL) values, respectively. The mean basal concentration of total cholesterol, HDL-cholesterol, and LDL-cholesterol was 193.37 ± 20.18 mg/dL, 60.05 ± 6.36 mg/dL, and 129.65 ± 14.50 mg/dL, respectively. HDL-cholesterol showed progressive increases in participants with desirable HDL-C > 60 mg/dL at 30 min (10 vs. 14 participants, p < 0.001) and at 120 min (10 vs. 16 participants, p < 0.001), while LDL-C peaked in participants with concentrations <100 mg/dL at 30 min (desirable cholesterol: 0 vs. 2, p = 0.001). HDL-C concentration showed differences after cannabis consumption, showing increases at 30 (63.25 ± 7.68 mg/dL) and 120 min (69.15 ± 18.67 mg/dL) and total cholesterol concentration changed to 180.95 ± 19.3 mg/dL (95%CI 172.5 to 189.4) at 120 min (p = 0.007). Conclusions: HDL-C cholesterol increased 30 and 120 min after Cannabis spp. ingestion, while LDL-C and total cholesterol showed partial reductions in heavy-users from Cusco, Peru.“